New compound from Euphorbia alatavica Boiss. Issue 3 (1st February 2019) - Rozimamat, Rushangul; Kehrimen, Nurmuhammat; Aisa, Haji Akber
Abstract: One new compound alatavinol (1 ), together with five known compounds, kaempferol (2 ), quercetin (3 ), laricircsinol (4 ), secoisolariciresinol (5 ) and loliolide (6 ) were isolated from the whole plant of Euphorbia alatavica Boiss. Those compounds were isolated and purified by various column chromatographic methods and their structures were elucidated by spectroscopic (1D, 2D NMR, and HR-MS) chemical analyses. All compounds were isolated for the first time from E. alatavica Boiss, and biochemical pathway of the new compound has been hypothesized. Furthermore, these compounds were evaluated for antioxidant properties based on the DPPH radical scavenging activities. Results showed that IC50 values of compounds1, 3, 4, 5 and6 were 25.69, 1.88, 2.87, 11.55 and 17.81 μg/mL, respectively, as compared to the control ascorbic acid (5.34 μg/mL). Abstract :